CFD Benchmark Tests for Indoor Environmental Problems: Part 2 Cross-Ventilation Airflows and Floor Heating Systems - Kazuhide Ito; Kiao Inthavong; Takashi Kurabuchi; Toshikatsu Ueda; Tomoyuki Endo; Toshiaki Omori; Hiroki Ono; Shinsuke Kato; Koji Sakai; Yoshihide Suwa; Hiroshi Matsumoto; Hajime Yoshino; et al. (International Journal of Architectural Engineering Technology, 2015)
Commercial Computational Fluid Dynamics (CFD) software is practically applied in indoor environmental design recent years but the prediction accuracy of CFD simulation depends on the understanding for the fundamentals of fluid dynamics and the setting of appropriate boundary and numerical conditions as well. Additionally, deeper understanding to a specific problem regarding indoor environment is also requested. The series of this study aimed to provide with the practical information such as prediction accuracy and problematic areas related to CFD applications in indoor environment, air conditioning and ventilation, then performed benchmark tests and reported the results. In this Part 2, benchmark test results for cross-ventilation airflows and floor heating systems were introduced. The highest reproducibility of the predicted results compared with the wind tunnel results occurred when the Z0-type wall function was used as the floor-surface boundary condition and the SST k–ω for the turbulence model in case of cross-ventilation flow and SST k–ω model showed also the closest matching results with experiment in case of natural convection in a room with floor heating.